IMPLEMENTASI METODE QIRA’AH SAB’AH DI MASJID SYAHRUN NUR SIPIROK - Abdul Wahid Harahap; Zainal Efendi Hasibuan; Sawaluddin Siregar; Syamsuddin Muir (Yayasan Baitul Hikmah al-Zain, 2024)
The main problem in this research is how effective the qira'ah sab'ah learning method used in the mosque is. The research method used is qualitative research with a case study approach. Data was collected through direct observation, interviews with teachers and congregants, as well as analysis of related documents. The research results show that learning qira'ah sab'ah at the Syahrun Nur Sipirok Mosque is effective in improving the Al-Qur'an reading skills of the congregation. Factors such as teacher competency, community support, and a conducive learning environment contribute to the success of this method. However, several challenges such as inconsistent participation levels from congregations and the need to increase human resources are still major concerns. So, learning qira'ah sab'ah at the Syahrun Nur Sipirok Mosque has proven to be effective by utilizing methods that are appropriate and supportive in terms of teaching and learning.